Cervical cancer screening programs in Latin America: current recommendations for facing elimination challenges - Ginna Fernández-Deaza; Maria Caicedo-Martínez; Beatriz Serrano; Esther Roura; Juan Sebastián Castillo; Silvia de Sanjosé; Laia Bruni; Raúl Murillo (Instituto Nacional de Salud Pública, 2022)
Objective. To describe current cervical cancer screening program guidelines in Latin America. Materials and methods. We searched official recommendations for the general population and women living with HIV (WLHIV) by reviewing official sources from 19 countries; these data were supplemented with a consultation carried out by the WHO with the Ministries of Health. Results. Screening policies vary significantly in regard to target populations, primary tests, and screening intervals. Sixteen countries have recently updated their recommendations; however, cytology remains the primary screening test for most countries. Eleven countries have introduced HPV tests, and eight countries have implemented screen-and-treat algorithms; only three countries have developed evidence-based guidelines. All countries but Costa Rica have specific recommendations for WLHIV. Conclusions. Although most countries have updated their screening policies, only a few are properly aligned with the WHO elimination strategy. Recommendations for WLHIV require better integration with cervical cancer screening programs.